PUBLIC DEBTS AND ECONOMIC DEVELOPMENT IN NIGERIA (1980-2023) (Journal of the Management Sciences, 2024)
The main objective of the study is to examine the effects of public debt on economic development. Human development index was used to proxy economic development while external debt, internal debt and debt servicing were used to proxy public debt. This study employs ex post facto research design using time series data for the periods under study (1980-2023). Data for this study is completely secondary in nature, sourced from various issues of Central Bank of Nigeria (CBN) Statistical Bulletins and World Development Indicator (WDI). The ARDL long-run estimates show that while External Debt (EXD) has a negative but statistically insignificant effect on human development, Debt Servicing (DTS) significantly harms human development by diverting resources from key sectors. Internal Debt (IND) has a small, statistically insignificant positive effect, suggesting it does not meaningfully impact human development on its own. Overall, high debt servicing costs negatively affect long-term growth, indicating a need for better management of both external and internal debt. To address the findings, focus on three key recommendations: 1) Improve management of debt servicing costs to prevent resource diversion from critical sectors like education and healthcare. 2) Reallocate resources to enhance human development by funding essential services despite debt obligations. 3) Increase transparency in debt management to build trust and ensure that debt practices support longterm growth and development.
Keywords: economic development, public debt, external debt, inter debt, debt servicing, Nigeria